Expression analysis of cathelicidin and NK‐lysin in Dabry's sturgeon (Acipenser dabryanus). (11th May 2019) - Han, Panpan; Tian, Guangming; Gao, Weihua; Yuan, Hanwen; Deng, Dan; Zhang, Wenbing; Xu, Qiaoqing
Abstract: Antimicrobial peptides (AMPs) are a conserved component of the innate immune response in many species. In the present study, the cDNA sequences encoding two AMPs (cathelicidin and NK‐lysin, comprising 1, 576 and 606 bp, respectively) were cloned from Dabry's sturgeon ( Acipenser dabryanus ). Phylogenetic analysis demonstrated that the two AMPs were clustered together with homologous protein sequences from other fish. NK‐lysin was highly expressed during early embryonic development, suggesting maternal transmission. Tissue distribution analysis showed that cathelicidin had the highest expression in the liver and NK‐lysin was most abundantly expressed in the spleen. In response to Poly I:C treatment, the expression of cathelicidin was upregulated at 12 and 24 hr post induction (hpi), but downregulated at 72 hpi. NK‐lysin mRNA expression increased after treatment with Poly I:C, reaching a peak at 24 hpi. Lipopolysaccharide treatment also induced the expression of two antimicrobial peptide genes. Lipopolysaccharide treatment significantly upregulated the expression of cathelicidin at 6, 24, and 48 hpi, and upregulated NK‐lysin expression at 6 and 12 hpi. These results suggested that two AMPs could participate in the immune response induced by poly I:C or LPS stimulation.